Factors Affecting The Main Hypertension Events in The Bukong Pandu Raya Village, West Kalimantan - Redjeki, Sri; G. Sri Redjeki; Fulgensius Surianto (Talenta Publisher, 2019)
Hypertension contributes 9.4 million deaths from cardiovascular disease each year. The cause of hypertension is because some people have a bad lifestyle, people often do not maintain their diet and people often eat salted and fatty foods. The purpose of this research is to find out the factors that influence Primary Hypertension in Dusun Bukong, Pandu Raya Village, West Kalimantan in 2018. This research method used quantitative methods with descriptive correlation design and cross sectional approach. By using the Slovin formula a total sample of 197 respondents was obtained. The results of the study, by conducting a univariate analysis found that most respondents had a level of knowledge related to hypertension (62.9%), more than half had a good lifestyle (58.4%), income above the MSE (57.9%) and more of half had hypertension (54.9%). From the bivariate analysis using the Kendall's Tau B test and Kendall's Tau C, the results of the study are found: there is a significant relationship between the level of knowledge (p value = 0,000), lifestyle (p value = 0,000) and income (p value = 0.047) with the incidence of hypertension . Discussion: Knowledge, lifestyle and family income in Dusun Bukong, Pandu Raya village have a significant relationship with the incidence of hypertension, so that health workers are expected to continue to provide support and motivation to the community to continue to improve their knowledge and a healthy lifestyle.